Bridging the Divide: The Role of Motivation and Self-Regulation in Explaining the Judgment-Action Gap Related to Academic Dishonesty - Stephens, Jason M. (Frontiers in Psychology, 2018)
There is often a divide between moral judgment and moral action; between what we believe we ought to do (or not do) and what we do. Knowledge of this divide is not new, and numerous theories have attempted to offer more robust accounts of ethical decision-making and moral functioning. Knowledge of widespread academic dishonesty among students is also not new, and several studies have revealed that many students report cheating despite believing it is wrong. The present study, involving cross-sectional survey data from a sample of secondary students (N= 380) in the United States, contributes to the literature on this important area of theory and research by fulfilling three broad purposes. The first purpose concerned the assessment of students’ judgments related to academic dishonesty, and offered evidence for the utility of a new instrument that measures what domain (personal, conventional, or moral) students use to categorize various types of cheating behaviour rather than how much they believe it to be wrong. The second purpose involved exploring the relations between domain judgments and engagement in academic dishonesty, and results provided evidence for the hypothesis that students who believed an action to be morally wrong would be less likely to report doing it. Finally, the third and most important purpose of the study involved bridging the divide between moral judgment and action of academic dishonesty by testing competing theoretical models of moral functioning. Results indicated that the data demonstrated the best fit to a modified version of the hypothesized four-component model, whereby self-regulation (in the form of selective moral disengagement) played a significant mediating role in the relations between moral judgment and academic dishonesty, and that moral judgment also affected self-regulation indirectly through moral motivation (i.e., responsibility judgments). In brief, findings from this study offer support for the contention that moral functioning is both multi-component and effortful. Moral judgment is important, but only one of several components needed for effective moral functioning, and motivation and self-regulation play critical mediating roles in helping to bridge the divide between judgment and action.